2018
DOI: 10.1080/08927014.2018.1434158
|View full text |Cite
|
Sign up to set email alerts
|

Anti-infection silver nanoparticle immobilized biomaterials facilitated by argon plasma grafting technology

Abstract: Many research groups have attained slow, persistent, continuous release of silver ions through careful experimental design using existing methods. Such methods effectively kill planktonic bacteria and therefore prevent surface adhesion of pathogens. However, the resultant modified coatings cannot provide long-term antibacterial efficacy due to sustained anti-microbial release. In this study, the anti-infection activity of AgNP immobilized biomaterials was evaluated, facilitated by argon plasma grafting technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(60 citation statements)
references
References 29 publications
4
55
0
Order By: Relevance
“…The system was evacuated to 360 mTorr as argon gas was introduced to the chamber at a flow rate of 0.068 m 3 h –1 . The chamber pressure was subsequently maintained at 360 mTorr. A radio frequency generator was supplied with a frequency of 13.56 MHz and had an output of up to 100 W for ca. 5 min.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The system was evacuated to 360 mTorr as argon gas was introduced to the chamber at a flow rate of 0.068 m 3 h –1 . The chamber pressure was subsequently maintained at 360 mTorr. A radio frequency generator was supplied with a frequency of 13.56 MHz and had an output of up to 100 W for ca. 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma technology has been utilized as an effective tool for the functionalization of polymeric material or synthesis of nanomaterials on transparent metal oxide films such as TiO 2 and to introduce desirable functional properties. Plasma-modified FTO (fluorine doped tin-oxide) electrodes with cobalt selenide nanomaterials have been shown to improve the performance in dye-sensitized solar cells . This has been attributed to the increase in surface hydrophilicity, nanoparticle packing density, higher dye loading, and improved electron transport and reduced recombination.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…AgNPs are promising agents in overcoming the bacterial infection with minimal chance of bacterial resistance due to minuscule concentration of AgNPs. Ambi and colleagues synthesized AgNPs with antibacterial activity (Ambi et al 2018). Bacterial colonization stimulates the activation of these AgNPs and it was found that they can effectively suppress the growth of Grampositive and Gram-negative bacteria such as Staphylococcus epidermis, methicillin-resistant Staphylococcus aureus, and E. coli.…”
Section: Discussionmentioning
confidence: 99%